A bacterial translation activator with an intrinsically disordered RNA-binding region - Pallabi Basu; Elizabeth A. Farland; James C. Charity; Kade A. Townsend; Simon L. Dove (Proceedings of the National Academy of Sciences, 2026)
Bacterial RNA-binding proteins (RBPs) that control the translation of multiple transcripts act largely as negative regulators. Here, we report the identification and characterization of a positive regulator of translation (called PhaF) in the opportunistic pathogen Pseudomonas aeruginosa . Using CLIP-seq and CLAP-seq we identify upward of 50 transcripts targeted by PhaF. We demonstrate that PhaF acts to stimulate the translation of target mRNAs by binding upstream of the Shine–Dalgarno sequence using one or more of the multiple KPAA motifs located in an intrinsically disordered region of the protein. Importantly, we show that PhaF plays a key physiological role in P. aeruginosa through its translational control of the pslA transcript required for exopolysaccharide synthesis and biofilm formation. Our findings uncover an activator of translation in bacteria that binds target transcripts using an RNA-binding region reminiscent of those that are prominent in eukaryotic RBPs.